PV energy and electric mobility – driving forces of the energy transition - Beister, Detlef; Leifert, T. (Grid Integration of Electric Mobility, 2017)
eMobility is the global key to an environmentally friendly transformation of mobility and, in Germany, it is part of the energy transition. The use of electric vehicles, particularly in combination with electricity from renewable energies, generates significantly less carbon dioxide. Thanks to their energy storage systems, electric vehicles will also be able to compensate for fluctuations in wind and solar power in a smart grid and thus support the development and market integration of these volatile energy sources. Germany, however, is trailing behind its stated political objectives in the field of eMobility, according to which the number of existing vehicles should have reached 100,000 by the end of 2014. The actual figure was 24,000.